Political Leadership and Economic Reform : The Brazilian Experience in the Context of Latin America - Cardoso, Fernando Henrique; Graeff, Eduardo (World Bank, Washington, DC, 2017)
Brazil grew 2.4 percent per year on average in the last 25 years-somewhat less than Latin America, a good deal less than the world, far less than the emerging countries of Asia in the same period, and indeed far less than Brazil itself in previous decades. If anything stands out favorably in recent Brazilian experience, it is not growth but stabilization and the successful opening of the economy. The purpose of this paper is more modest. It is limited to setting out the authors' particular view of recent efforts to consolidate democracy in Brazil while controlling inflation and resuming economic growth. At the same time the paper presents, as objectively as possible, some thoughts on the limits but also the relevance of action by political leaders to set a course and circumvent obstacles to that process. Here and there, the paper refers to the experiences of other Latin American countries, especially Argentina, Chile, and Mexico, not to offer a full fledged comparative analysis but merely to note contrasts and similarities that may shed light on the peculiarities of the Brazilian case and suggest themes for a more wide-ranging exchange of views.